The Effectiveness Of An Internship Program: A Case Study At PT Kulina Putra Madya - Faruq, Daffa Al; Linando, Jaya Addin (UNIVED Press, 2026)
This study examines the effectiveness of the Certified Internship and Independent Study Program (MSIB) through a qualitative case study of interns placed at PT Kulina Putra Madya (KPM) under APINDO coordination. Despite the program’s promise of strategic roles as